Factors influencing the happiness of male correctional officers: A cross-sectional study in South Korea. - Hyun-Ok Jung; Seung-Woo Han (PLoS ONE, 2024)
Purpose This study is a descriptive research study using a self-reported survey method to determine the impact of correctional officers' job satisfaction, leisure satisfaction, and family strengths on their happiness. Methods This study targeted 269 male correctional officers working in correctional facilities established in P and S cities. The tools used in this study were job satisfaction, leisure satisfaction, and family strengths and happiness. The collected data were analyzed using the SPSS/WIN 22.0 program according to the research purpose. Data analysis included descriptive statistics, analysis of differences in happiness according to demographic characteristics, correlations between variables, and finally, analysis of factors affecting happiness through multiple linear regression. Results As a result of this study, job satisfaction(β = 0.081, p = 0.036), leisure satisfaction(β = 0.078, p = 0.001), and family strengths(β = 0.081, p = 0.001) were found to be factors affecting the happiness of male correctional officers, and the explanatory power of these variables was found to be 26.0%. Conclusion Based on the results of this study, it is necessary to identify factors that affect the happiness of male correctional officers and provide various counseling and program interventions that can contribute to improving happiness.